Manajemen Media Komunikasi pada Aplikasi ASSiK di Surabaya dalam Perspektif Islam - Rachman, Rio Febriannur (Idarotuna : Journal of Administrative Science, 2025)
Following the COVID-19 epidemic, digital transformation in public services has emerged as a strategic imperative. This study looks at how the Surabaya City Government's digital innovation in the employment sector, the ASSiK (Arek Suroboyo Siap Kerjo) application, is managed through communication medium. This study examines how user experiences with ASSiK are framed as a kind of technology, spiritual values, and social interaction using a qualitative approach and phenomenological approaches. The study's findings demonstrate that ASSiK serves as a two-way public communication platform that is inclusive, transparent, and flexible in addition to being a digital job recruitment platform. The principles of Maqasid Sharia in Islam, particularly the protection of life (hifz al-nafs), property (hifz al-mal), and reason (hifz al-‘aql), are in line with this innovation, which also helps to achieve the Sustainable Development Goals (SDGs), particularly goal 8 on decent work and economic growth. The results of the study show that ASSiK is a symbol of moral and welfare-focused public policy in addition to being an administrative tool. In order to enhance the ethical aspect of public service in the age of technological revolution, this study suggests incorporating Islamic principles into digital innovation governance.